2015
DOI: 10.1080/10242694.2015.1025485
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of ETA’s Dissolution on Domestic Tourism in Spain

Abstract: In late 2011, the Spanish terrorist organization ETA announced the end of armed violence after more than forty years of illegal activity. While the existing literature has already established the negative impact of terrorist actions on international tourism in a particular region, this paper aims to determine whether ETA's final ceasefire and definitive dissolution had a positive impact on domestic tourism in Basque Country. To that end, a directed gravity model is estimated over a panel data-set of 699 domest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
0
20
1
Order By: Relevance
“…This finding points to some interesting insights that can only be gained by employing (quasi) experimental studies. Repeated measures are required and it is necessary to look at more than one destination a time (Voltes‐Dorta et al ., ). Looking at individual destinations over the years may easily lead to the conclusion that risk perceptions and therefore the number of visiting tourists to each destination fluctuate because of the occurrence of different dramatic events.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding points to some interesting insights that can only be gained by employing (quasi) experimental studies. Repeated measures are required and it is necessary to look at more than one destination a time (Voltes‐Dorta et al ., ). Looking at individual destinations over the years may easily lead to the conclusion that risk perceptions and therefore the number of visiting tourists to each destination fluctuate because of the occurrence of different dramatic events.…”
Section: Discussionmentioning
confidence: 99%
“…Volters‐Dorta et al . () point towards the need for such studies, and the present findings highlight their importance. This is because insights gained from the present findings diverge from what would have been concluded from looking at one destinations at a time.…”
Section: Limitations and Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…However, reviewing 36 peer-reviewed studies on the effect of terrorism on tourism, Voltes-Dorta, Jiménez, and Suárez-Alemán (2015) concluded that the reported study by Wolff and Larsen (2014) was the only one that did not reach the expected conclusion that terrorism had a negative effect on tourism. Seemingly, the 22nd of July attacks studied by Wolff and Larsen (2014) have some characteristics that are not shared by most of the terror attacks reported in the literature, which may be the reason why risk perceptions decreased in this particular case, but not in the other cases.…”
Section: Literature Reviewmentioning
confidence: 97%